DOI: 10.11606/d.88.2011.tde-25042011-090409
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do efeito do ambiente no comportamento em fadiga de novas ligas 'AL' de grau aeronáutico

Abstract: Lithium-containing aluminum alloys are known to be attractive materials because of their low densities, high elastic modulus, high strengths and good corrosion resistance. Material degradation due to fatigue and corrosion are two major factors that contribute to the aging of an aircraft, and the prediction of corrosion and corrosion-fatigue are very important for the structural integrity of aircrafts. The presence of corrosion pits can significantly shorten the fatigue crack initiation life and decrease the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
4
0
2
Order By: Relevance
“…Further investigation is on the way using transmission electron microscope to make a detailed characterization of the microstructure. Difference in roughness would be another possibility, however as verified by Gamboni 21 the specimens from both alloys presented similar roughness.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Further investigation is on the way using transmission electron microscope to make a detailed characterization of the microstructure. Difference in roughness would be another possibility, however as verified by Gamboni 21 the specimens from both alloys presented similar roughness.…”
Section: Resultsmentioning
confidence: 82%
“…It is observed that in air, without the preconditioning, the AA2524-T3 alloy presented slightly better fatigue resistance than the AA2198-T851. The fracture surface analysis carried out by Gamboni and presented elsewhere 21 has shown that all the crack nucleation sites were located at the specimens' surface. The surface is weaker than the interior metal in the same state, since at the surface the atoms do not have neighbors, and it is likely that the stress to cause plastic flow for these atoms is slightly lower than at interior.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Segundo Gamboni (2011) para aplicações práticas, o alumínio possui elementos de liga como Cu, Mg, Mn, Zn, Li e Si com a finalidade de aumentar sua resistência mecânica ou ainda sua resistência específica, entretanto estes elementos formam compostos intermetálicos, os quais tem um efeito prejudicial nas propriedades de corrosão do material, devido a formação de um filme óxido mais fino e mais condutor que permite a ocorrência de reações catódicas.…”
Section: Min Maxunclassified
“…Posteriormente, as placas foram submetidas a carregamento axial com amplitude constante e razão de carregamento igual a 0,1. A pesquisa revelou que o Al 7050-T7451 é susceptível ao surgimento de pites quando imerso em ambiente corrosivo e que há uma redução significativa da vida em fadiga devido a presença dos pites Gamboni (2011). conduziu em ensaios de fadiga no Al 7050-T7451 após sua exposição, por 15 dias, à névoa salina com concentração de 5% de NaCl.…”
unclassified